2002
DOI: 10.1016/s0896-6273(02)00802-4
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Dependent Protein Kinase Regulates Desensitization of the Capsaicin Receptor (VR1) by Direct Phosphorylation

Abstract: The capsaicin receptor, VR1 (also known as TRPV1), is a ligand-gated ion channel expressed on nociceptive sensory neurons that responds to noxious thermal and chemical stimuli. Capsaicin responses in sensory neurons exhibit robust potentiation by cAMP-dependent protein kinase (PKA). In this study, we demonstrate that PKA reduces VR1 desensitization and directly phosphorylates VR1. In vitro phosphorylation, phosphopeptide mapping, and protein sequencing of VR1 cytoplasmic domains delineate several candidate PKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
463
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(483 citation statements)
references
References 26 publications
10
463
4
Order By: Relevance
“…It has been demonstrated that cAMPdependent PKA activation can enhance capsaicin-induced inward current and Ca 2ϩ transient in dorsal root ganglion neurons (36) as well as in vagal sensory neurons (12,22). Indeed, recent studies have successfully delineated several candidate PKA-phosphorylation sites in TRPV1, through which PKA may mediate the sensitization of this channel as well as prevent its desensitization (2).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that cAMPdependent PKA activation can enhance capsaicin-induced inward current and Ca 2ϩ transient in dorsal root ganglion neurons (36) as well as in vagal sensory neurons (12,22). Indeed, recent studies have successfully delineated several candidate PKA-phosphorylation sites in TRPV1, through which PKA may mediate the sensitization of this channel as well as prevent its desensitization (2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PKC-mediated phosphorylation also decreases the heat threshold of channel activation (5,6). Similarly, phosphorylation of the N terminus with PKA affects TRPV1 channel function by modulating the rate and extent of receptor desensitization (9). In addition, the C-and N termini display the presence of putative lipid-protein and protein-protein interacting domains that may also contribute to the regulation of receptor channel properties.…”
mentioning
confidence: 99%
“…The desensitization of capsaicin-evoked currents is dependent on external Ca 2ϩ and presumably upon the activity of a Ca 2ϩ -dependent phosphatase (16,17). Recently, Bhave et al (20) suggested that protein kinase A (PKA) controls tachyphylaxis, the reduced response to repeated stimuli. However, the molecular mechanism of VR1 desensitization has remained elusive.…”
mentioning
confidence: 99%